LAYING-OUT CALCULATION OF TRANSVERSE CROSS-SECTIONS WHILE CONSTRUCTING LINEARLY EXTENDED EARTHWORK STRUCTURES - M. S. Nesterenok; N. G. Madalinskaya (Наука и техника)
Course books and industrial manuals do not cite exact formulae for calculation of cross-section area of the extended earthwork structures for slope site sections. The paper considers a variant of such calculations which are necessary for better certainty in determination of earth scope and accurateness in geodetic laying-out works while constructing linearly extended earthwork structures on the sloped ground surface.